Factors Affecting Financial Statement Fraud In State-Owned Enterprises Listed On The Idxbumn20 Index In 2018-2022 Based On The Fraud Pentagon Theory - Satria, Bayu Dwi; Fachriyah, Nurul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to determine whether Financial Target, Ineffective Monitoring, Change in Auditor, CEO’s Education, and Frequent Number of CEO’s Picture affect financial statement fraud. The samples of this research include 14 IDXBUMN20 companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022, selected through purposive sampling. The data are analyzed by logistic regression processed by IBM SPSS Statistics 22 software. The result of this research exhibit that Ineffective Monitoring and CEO’s Education affect financial statement fraud while Financial Target, Change in Auditor, and Frequent Number of CEO’s Picture do not affect financial statement fraud.